Characteristic And Distribution Pattern Of Small And Medium Metals Industries In Citeureup District, Bogor Regency - Japar Sidiq; Janthy Trilusianthy Hidayat; Rudi Mahmud Zafrullah (Interdisciplinary Social Studies, 2025)
The Bogor Regency Government has designated Citeureup Subdistrict as a thematic cluster for leading metal products in Bogor Regency. Small and medium-sized industries will develop more rapidly if they are located in areas with conditions suitable for industrial development. This study aims to analyze the characteristics and distribution patterns of small and medium-sized metal industries in Citeureup Subdistrict, Bogor Regency. Primary data collection was conducted through field observations and validation, interviews, questionnaires, and documentation. Secondary data collection was carried out through literature reviews. The analytical methods used include descriptive analysis to examine characteristics and nearest neighbor analysis to analyze the distribution patterns of small and medium-sized metal industries. The analysis results show that there are 317 small and medium-sized metal industries in Citeureup Subdistrict, spread across 4 villages, namely Sukahati Village, Pasir Mukti Village, Tarikolot Village, and Gunungsari Village. The products produced are classified into household appliances, medical equipment, automotive components, construction equipment, and other metal products. The marketing reach includes local, regional, and national scales. The results of the nearest neighbor analysis, assisted by ArcGIS 10.8 software, indicate that the spatial distribution of small and medium-sized metal industries in Citeureup Subdistrict follows a cluster pattern, involving a complete range of actors, including the central government, local government, universities, and other associations.